Necrozone. Extreme Violence and Juvenicide in the Huachicol Triangle in Guanajuato 2018-2024 (Andamios, Revista de Investigación Social, 2025)
The constitution of a necrozone in the Huachicol Triangle in Guanajuato, Mexico, is analyzed through experiences of extreme violence towards young people. The concepts of extreme violence, biopolitics, necropolitics and juvenicide are addressed, thus exploring how these dynamics are territorialized, forming the necrozone. The methodology uses the ethnography of violence approach. The findings reveal the interaction between organized crime cartels, state forces and the civilian population, where violence has been normalized and silence has become a central characteristic in the face of semiotic events with high cruelty and sadism. It is concluded that in the necrozone the lives of young people are devalued, reflecting a broader crisis of governance and human rights.
Keywords: necrozone; extreme violence; juvenicide; biopolitics; necropolitics